Gold-ionic liquid nanofluids with preferably tribological properties and thermal conductivity - Wang Baogang; Wang Xiaobo; Lou Wenjing; Hao Jingcheng (Nanoscale Research Letters, 2011)
Abstract Gold/1-butyl-3-methylimidazolium hexafluorophosphate (Au/[Bmim][PF6]) nanofluids containing different stabilizing agents were fabricated by a facile one-step chemical reduction method, of which the nanofluids stabilized by cetyltrimethylammonium bromide (CTABr) exhibited ultrahighly thermodynamic stability. The transmission electron microscopy, UV-visible absorption, Fourier transform infrared, and X-ray photoelectron characterizations were conducted to reveal the stable mechanism. Then, the tribological properties of these ionic liquid (IL)-based gold nanofluids were first investigated in more detail. In comparison with pure [Bmim][PF6] and the nanofluids possessing poor stability, the nanofluids with high stability exhibited much better friction-reduction and anti-wear properties. For instance, the friction coefficient and wear volume lubricated by the nanofluid with rather low volumetric concentration (1.02 × 10-3%) stabilized by CTABr under 800 N are 13.8 and 45.4% lower than that of pure [Bmim][PF6], confirming that soft Au nanoparticles (Au NPs) also can be excellent additives for high performance lubricants especially under high loads. Moreover, the thermal conductivity (TC) of the stable nanofluids with three volumetric fraction (2.55 × 10-4, 5.1 × 10-4, and 1.02 × 10-3%) was also measured by a transient hot wire method as a function of temperature (33 to 81°C). The results indicate that the TC of the nanofluid (1.02 × 10-3%) is 13.1% higher than that of [Bmim][PF6] at 81°C but no obvious variation at 33°C. The conspicuously temperature-dependent and greatly enhanced TC of Au/[Bmim][PF6] nanofluids stabilized by CTABr could be attributed to micro-convection caused by the Brownian motion of Au NPs. Our results should open new avenues to utilize Au NPs and ILs in tribology and the high-temperature heat transfer field.